2015
DOI: 10.1590/1807-2577.1079
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health in patients under conventional and lingual orthodontic therapies

Abstract: ObjectiveSome clinical periodontal health parameters were assessed comparatively in patients using conventional and lingual brackets.Material and methodA trained examiner registered the frequencies of visible plaque (VP), bleeding on probing (BOP), as well as the simplified oral hygiene (OHI-S) and modified gingival (MGI) indices in 83 subjects from two clinics. The effects of orthodontic treatments on periodontal health were analyzed using logistic regression (α = 0.05).ResultIn the conventional group, the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…54 Also, it has been shown that patients with a labial appliance experience significantly higher frequency of gingivitis in posterior maxillary teeth, but patients with lingual appliances experience it more often in lingual anterior teeth. 55 Regarding the bleeding on probing (BOP) and PD, some studies have shown the significant increase of PD and BOP, 56-58 and the others have stated no significant differences. 56,58-61 Therefore, further studies are required to prove the effects of lingual appliances on these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…54 Also, it has been shown that patients with a labial appliance experience significantly higher frequency of gingivitis in posterior maxillary teeth, but patients with lingual appliances experience it more often in lingual anterior teeth. 55 Regarding the bleeding on probing (BOP) and PD, some studies have shown the significant increase of PD and BOP, 56-58 and the others have stated no significant differences. 56,58-61 Therefore, further studies are required to prove the effects of lingual appliances on these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was seen that these parameters were primarily adjusted three months after the removal of brackets. Although lingual therapy is considered the most visually appealing orthodontic treatment due to the absence of visible brackets and the absence of protruding lips, there have been multiple reports of discomfort, changes in speech, and difficulties in maintaining proper oral hygiene [15,16] .…”
Section: Introductionmentioning
confidence: 99%